Virtual Leadership Competence of Elementary School Principals in Makassar City - Arismunandar, Arismunandar; Wahed, Andi; Emmiyati, Nuri (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
The COVID-19 pandemic has brought significant innovations in the education sector, including the transformation of school principals' leadership from conventional to virtual forms. This study aims to examine the level of virtual leadership competence among elementary school principals in Makassar City. A mixed-method approach with a sequential explanatory design was employed, in which quantitative data analysis informed the qualitative phase. Quantitative data were analyzed using descriptive statistical techniques. In contrast, qualitative data were analyzed using the interactive model developed by Miles, Huberman, and Saldana (2014), which consists of data collection, data condensation, data display, and conclusion drawing or verification. The results show that the principals' virtual leadership competence is at a very high level, with an average score of 72.78 (53%), which falls within the score range of 72 < X < 90. This competence is demonstrated through six key indicators: e-communication, e-social, e-team, e-change, e-tech, and e-trust. The high level of competence is attributed to principals' proactive roles in maintaining teacher performance and ensuring the quality of educational services during online learning. The study highlights the shift in leadership dynamics and contributes new insights into the digital competencies required of school principals in a post-pandemic educational landscape.